2015
DOI: 10.1007/s10853-015-8835-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of polystyrene-block-poly(vinylbenzoic acid): a promising compound for manipulating photoresponsive properties at the nanoscale

Abstract: Using reversible addition-fragmentation chain transfer (RAFT) polymerization, the effect of PSt macro-RAFT and 4VBA ratio on the synthesis of a carboxylic acid functional block copolymer (PSt-b-P4VBA) was studied. PSt macroRAFT polymer was initially prepared followed by the insertion of 4-vinylbenzoic acid (4VBA) monomer. The chemical structure of the diblock copolymer was confirmed by NMR and FTIR. The effect of PSt macroRAFT and 4VBA ratio on copolymerization yield and on molecular weight distribution was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The second weight loss, which started from 350°C, is attributable to polymer backbone degradation, which is similar for all polymers. The degradation of polymers was completed after 500°C, the remaining weight of char 37 obtained by chemical reactions of organic substance was also consistent with the carboxylic acid concentration in the polymer chain. The carboxylic acid group might cause dehydration, carbonization, and oxidation, resulting in more char remaining in the polymer with the higher carboxylic acid group concentration.…”
Section: Resultssupporting
confidence: 66%
“…The second weight loss, which started from 350°C, is attributable to polymer backbone degradation, which is similar for all polymers. The degradation of polymers was completed after 500°C, the remaining weight of char 37 obtained by chemical reactions of organic substance was also consistent with the carboxylic acid concentration in the polymer chain. The carboxylic acid group might cause dehydration, carbonization, and oxidation, resulting in more char remaining in the polymer with the higher carboxylic acid group concentration.…”
Section: Resultssupporting
confidence: 66%
“…The thermal decomposition temperature of the pure ZIF‐8 nanocrystals was 610 °C, which indicated that the ZIF‐8 nanocrystals had good thermal stability. PVBA 42 ‐ b ‐PS 36 and PVBA 42 ‐ b ‐PS 42 showed the degradation of carboxylic groups of their PVBA blocks from 100 to 350 °C and the degradation of their polymer backbones at 450 °C . The percentage of carboxyl groups was approximately 15.7 % and 13.0 % in PVBA 42 ‐ b ‐PS 36 and PVBA 42 ‐ b ‐PS 42 , respectively, which indicated that the mole ratio of PS to PVBA was 0.86:1 in PVBA 42 ‐ b ‐PS 36 and 1:1 in PVBA 42 ‐ b ‐PS 42 .…”
Section: Resultsmentioning
confidence: 96%
“…No peaks were observed at 1843 and 2600 cm −1 (assigned to N−H stretching vibrations of HmeIM and the N−H⋅⋅⋅N hydrogen bond, respectively) owing to deprotonation and coordination with Zn 2+ of HmeIM . The peaks at 1690 and 1250 cm −1 represent the C=O and C−O stretch vibrations of carboxylic acid in PVBA blocks, respectively . In the FTIR spectra of PVBA 42 ‐ b ‐PS 36 /ZIF‐8 and PVBA 42 ‐ b ‐PS 42 /ZIF‐8, the appearance of the typical peaks of ZIF‐8 (1415 and 1299 cm −1 ) and the disappearance of the peaks at 1690 and 1250 cm −1 demonstrate that ZIF‐8 nanocrystals were anchored to the surface of the polymeric aggregates.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…[10][11][12] In particular, this method has been used to prepare amphiphilic poly(styrene-b-4-vinylbenzoic acid) block copolymers. 13,14 Furthermore, statistical poly(styrene-co-4-vinylbenzoic acid) copolymers have been prepared by free radical polymerization either in homogenous solution 15,16 or in emulsion. 17 However, the preparation of entangled, well-defined statistical poly(styrene-co-4vinylbenzoic acid) by RAFT polymerization has not previously been the subject of detailed investigations to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%